Private sector corruption, public sector corruption and the organizational structure of foreign subsidiaries - Sartor, Michael A. ca. 20./21. Jh. (Journal of business ethics, 2020)
Corporate anti-corruption initiatives can make a substantial contribution towards curtailing corruption and advancing efforts to achieve the United Nations’ Sustainable Development Goals. However, researchers have observed that underdeveloped assumptions with respect to the conceptualization of corruption and how firms respond to corruption risk impeding the efficacy of anti-corruption programs. We investigate the relationship between the perceived level of corruption in foreign host countries and the organizational structure of subsidiary operations established by multinational corporations (MNCs). Foreign host market corruption is disaggregated into two components - private and public corruption. We employ an uncertainty-based perspective grounded in transaction cost theory to focus upon the distinct mechanisms through which private and public corruption can each be expected to impact a foreign subsidiary’s organizational structure [wholly-owned subsidiary (WOS) or a joint venture (JV) with a local partner]. We expect that each type of corruption fosters a different type of uncertainty (environmental or behavioral) which predominates in shaping the MNC’s choice of foreign subsidiary investment structure. Hypotheses are developed and tested with a sample of 187 entries into 19 foreign host markets. Each type of corruption was found to exert a distinct effect upon the organizational structure of foreign subsidiaries. More precisely, while heightened perceived levels of public corruption were found to motivate MNCs to invest through a JV with a local partner rather than a WOS, more pronounced private corruption precipitated the opposite outcome.